1990
DOI: 10.1104/pp.93.4.1426
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Uptake of Nitrate in Barley

Abstract: 8,11,18,20,23,29 N03-PretreatmentsEffects of four different NO3-pretreatments on the kinetics of NO3-influx were investigated in 7 d old plants. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
407
2
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(451 citation statements)
references
References 18 publications
40
407
2
2
Order By: Relevance
“…The HATS is involved in nitrate uptake at low external nitrate concentrations (as low as 1 lM) while the LATS operates at higher concentration ([0.5 mM) (see review by Nacry et al 2013). Both systems possess a constitutive component (cHATS; cLATS) and an inducible component (iHATS; iLATS) (Siddiqi et al 1989(Siddiqi et al , 1990Faure-Rabasse et al 2002). Among the nine LjNPF genes studied in L. japonicus, expression of only CM0608.1210 was induced by nitrate.…”
Section: Function Of Nitrate Transport In Legumes Role Of Transportermentioning
confidence: 99%
“…The HATS is involved in nitrate uptake at low external nitrate concentrations (as low as 1 lM) while the LATS operates at higher concentration ([0.5 mM) (see review by Nacry et al 2013). Both systems possess a constitutive component (cHATS; cLATS) and an inducible component (iHATS; iLATS) (Siddiqi et al 1989(Siddiqi et al , 1990Faure-Rabasse et al 2002). Among the nine LjNPF genes studied in L. japonicus, expression of only CM0608.1210 was induced by nitrate.…”
Section: Function Of Nitrate Transport In Legumes Role Of Transportermentioning
confidence: 99%
“…The HATS is described as a saturable system, whereas the nature of the LATS is still not clear. Doddema & Telkamp (1979) and Goyal & Huffaker (1986b) found a second saturable system, but Siddiqi et al (1990) and Aslam, Travis & Huffaker (1992) observed a linear non-saturable component under higher concentrations of nitrate. Aslam et al (1992) even found two saturable, possibly constitutive systems in the low concentration range and a linear system at more than 500 mmol m -3 nitrate.…”
Section: Introductionmentioning
confidence: 99%
“…Aslam et al (1992) even found two saturable, possibly constitutive systems in the low concentration range and a linear system at more than 500 mmol m -3 nitrate. Despite some evidence that the LATS is of a passive nature Siddiqi et al 1991), it appears more likely that HATS and LATS both proceed thermodynamically uphill (King, Siddiqi & Glass 1992). In the papers mentioned above, two methods were used for exploring the kinetics: the first monitoring the depletion of nitrate from the external medium and the second following the movement of tracers (for a review, see Peuke & Kaiser 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Siddiqi et al (1989Siddiqi et al ( , 1990, we also introduced a negative feedback of root nitrate concentration on the parameters related to HATS and LATS functions (eqn 5). The rate of nitrate net uptake (eqn 6) is calculated from the nitrate influx weighted by a parameter accounting for nitrate efflux [r influx:net uptake , estimated from Devienne et al (1994)] and root carbohydrate concentration (eqn 7).…”
Section: Nitrate Uptake By Roots and Concentration In Soilmentioning
confidence: 99%